2022
DOI: 10.1371/journal.pbio.3001831
|View full text |Cite
|
Sign up to set email alerts
|

GBPL3 localizes to the nuclear pore complex and functionally connects the nuclear basket with the nucleoskeleton in plants

Abstract: The nuclear basket (NB) is an essential structure of the nuclear pore complex (NPC) and serves as a dynamic and multifunctional platform that participates in various critical nuclear processes, including cargo transport, molecular docking, and gene expression regulation. However, the underlying molecular mechanisms are not completely understood, particularly in plants. Here, we identified a guanylate-binding protein (GBP)-like GTPase (GBPL3) as a novel NPC basket component in Arabidopsis. Using fluorescence an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 70 publications
0
25
0
Order By: Relevance
“…Despite successful application of TID-based proximity labelling in plant cells at different sub cellular localisations (Mair et al, 2019; Tang et al, 2022; Arora et al, 2020; Xu et al 2021), it has always been questioned if it would work in plastids of higher plant cells as well. Reports on the free biotin concentration suggested only marginal amounts inside chloroplasts (Badelt et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Despite successful application of TID-based proximity labelling in plant cells at different sub cellular localisations (Mair et al, 2019; Tang et al, 2022; Arora et al, 2020; Xu et al 2021), it has always been questioned if it would work in plastids of higher plant cells as well. Reports on the free biotin concentration suggested only marginal amounts inside chloroplasts (Badelt et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…TurboID applications to identify protein-protein interaction networks in Arabidopsis and N. benthamiana used only 50-200 µM of exogenously added biotin but similar labeling times of 0.5-12 h, although strong protein biotinylation was observed already after as little as 15 min (Mair et al, 2019; Zhang et al, 2019; Xu et al, 2021; Tang et al, 2022; Wurzinger et al, 2022). While in these studies no effects on naturally biotinylated proteins was reported, we observed strong effects in Chlamydomonas with loss of natural protein biotinylation correlating with TurboID expression levels (Figures 2B, 2C, 3A, 4A; Supplemental Figure S7B).…”
Section: Discussionmentioning
confidence: 99%
“…In land plants, a desalting step was essential to remove excess biotin from protein extracts prior to incubation with streptavidin beads (Mair et al, 2019; Zhang et al, 2019; Arora et al, 2020; Xu et al, 2021; Tang et al, 2022; Wurzinger et al, 2022). This desalting step was required for Chlamydomonas only if biotin was added to crude membrane extracts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations